Years of the Maritime Continent. Issue 12 (15th June 2020) - Yoneyama, K.; Zhang, C.
Abstract: Years of the Maritime Continent (YMC) is a multiyear international program with participants from over 15 countries. Its overarching goal is to expedite the progress toward improving understanding and prediction of the local oceanic and atmospheric multiscale variability of the Indo‐Pacific Maritime Continent (MC) and its global impacts. YMC is motivated by the unique role of the MC in both the local and global weather climate systems, our lack of understanding of the key processes governing this role, and persistent systematic biases and errors in numerical model output for the region. YMC builds a comprehensive observational data set of the MC weather climate system, encourages observation‐modeling integration, and educates the next generation of scientists who will be the core workforce and leaders to further advance the study of the MC. Plain Language Summary: Years of the Maritime Continent is a multiyear international program to study the weather climate system of the Indo‐Pacific Maritime Continent and its global impacts. Systematic biases in regional rainfall produced by numerical forecast and climate models and incomplete knowledge of the regional weather climate system motivated this program. This program conducts field campaigns to collect atmospheric and oceanic observations. Its preliminary results reveal new information that encourage further researches by combining observations with numerical models. This article also serves as a solicitation for contributions to a cross‐organization special collection of publications in journals of seven professional organizations. This special collection is intended to promote further studies on the diverse nature of the weather climate system of the Maritime Continent. Key Points: The Indo‐Pacific Maritime Continent (MC) plays a pivotal role in the global weather climate system Years of the Maritime Continent (YMC) is an international program to improve understanding and prediction of local variability of the MC and its global impacts Preliminary results from YMC reveal new information on physical processes key to multiscale variability in the MC